ECO-EXTRACTION PROCESS OF ESSENTIAL OIL OF THE VEGETAL SPECIES EUCALYPTUS CAMALDULENSIS DEHNH.: PARAMETRIC MODELING AND OPTIMIZATION BY BOX-BEHNKEN PLAN - ABIDI Abdenabi ,a,b,* ,a ,c d and; DJERMANE Mohamed; IEZID Mostepha; GHERRAF Noureddine; PONTIE Maxime (Editura Academiei Romane/Publishing House of the Romanian Academy, 2023)
This study was aimed to implement response surface methodology to optimize the hydrodistillation parameters of the essential oil of the plant species Eucalyptus camaldulensis (RSM). The distillation time, condensation flow rate, and particle size were the desired parameters. To generate factor combinations, a three-factor Box-Behnken design was used. The response surface analysis yielded a linear model, which was used to calculate the top yield of extracted oil based on the optimized conditions. ANOVA shows that the generated polynomial model was highly noteworthy, with R2=0.861. The peak yield was 0.513663% at the optimal conditions, which were 1 mm as particle size, 3.4 mL/min as condensation flow rate, and 210 min as extraction time. The GC/MS analysis revealed the presence of p-cymene (26.22%), spathulenol (16.71%), and 1.8-cineole (14.44%) as major components.